Assessment of water balance using SWAT – A case study of the Nakhon Ratchasima Province - P. Kosa; T. Sukwimolseree (International Association of Lowland Technology, 2018)
In the dry season, the Nakhon Ratchasima province is facing a water scarcity problem in every year due to the gap between demand and supply of the water system. However, there are the high rainfall and runoff during rainy season. Then, the purposes of this study are to analyze the water balance and to manage the water resources in Nakhon Ratchasima province using SWAT. The study can be presented that, during dry season, the total amount of water demand is higher than the amount of runoff for the Lam Takhlong basin, Lam Phra Phloeng basin, Lam Sae basin, Lam Plai Mat basin, and Lam Chakkarat basin. However, this water demand can be supported by the maximum water storage in the reservoir. On the other hand, the total amount of water demand is less than the amount of runoff for Lam Choengkrai basin, Upper part of Lam Nam Mun basin, Lam Sa Thaet basin, and Second part of Lam Nam Mun basin. The excess water runoff from Lam Choengkrai basin should be diverted to Lam Takhlong basin and water diversion from Upper part of Lam Nam Mun basin should be considered for Lam Phra Phloeng basin and Lam Sae basin.